Formation of scientific research competences based on curriculum design in a human medicine faculty - Romaní Romaní, Franco Ronald (2022)
Competency-based learning in scientific research in the medicine faculties has been the subject of several theoretical approaches and many implementation experiences worldwide. We present the experience of an private university located in the city of Lima, Peru. This university has implemented a strategy of «research-based teaching» in conjunction with «research-oriented teaching» in order to incorporate the achievement of competences for scientific research in the curricular design. The experience is added to those described in medical schools, but with the appropriateness regarding the context of medical education in Peru. The implementation of the curricular strategy has generated unforeseen challenges in the formulation of the intervention, which are described for consideration in new scenarios. The experience is based on a conceptual framework that can serve as a reference for its application in other institutions at Latin America.